Transplants of Rat Chondrocytes Evoke Strong Humoral Response against Chondrocyte-Associated Antigen in Rabbits - Anna Osiecka-Iwan; Anna Hyc; Jaroslaw Józwiak; Aldona Komar; Justyna Niderla; Stanislaw Moskalewski (Cell Transplantation, 2003)
Rat chondrocytes transplanted intramuscularly in rabbits produced cartilage. In 1-day-old transplants chondrocytes remained viable. After 1 week peripheral chondrocytes of the transplant were dead and the cartilage was surrounded and resorbed by macrophages. In 2-week-old transplants cartilage deteriorated and was invaded by fibroblast-like cells and macrophages. Sera of rabbits that received two or three consecutive transplants of rat chondrocytes with 2-week intervals contained high titer of antichondrocyte cytotoxic antibodies. A part of the cytotoxic activity could be removed by absorption with rat splenocytes. Western blot analysis of lysates from fresh or 24-h cultured chondrocytes with absorbed sera detected antigen with M r of ~74 and ~23 kDa. Only the latter remained after reduction in 2-mercaptoethanol. In lysates of fibroblasts and endotheliocytes the 23-kDa antigen was not found but the serum reacted with M r 39-kDa antigen. In lysates of thymocytes a weak band corresponding to M r of 35 kDa was present. Serum from rabbits receiving transplants of living chondrocytes followed by chondrocytes suspended in complete Freund's adjuvant contained antibodies directed against components of crude collagenase used for cell isolation. Such antibodies could not be detected in sera of rabbits receiving transplants of living chondrocytes only. Molecular weight of detected antigen differs from that of collagen type II, core of aggrecan, link proteins, and several other macromolecules of cartilage matrix. It could represent either a component of chondrocyte membrane or a membrane-bound substance resistant to enzymes used for isolation. Availability of antibodies against presumably chondrocyte-specific antigen produced during transplant rejection may help to characterize it more precisely and to ascertain whether its presence may influence results of autogenous chondrocyte transplants in humans.